2009
DOI: 10.1128/iai.01561-08
|View full text |Cite
|
Sign up to set email alerts
|

Functional Comparison of the Binding of Factor H Short Consensus Repeat 6 (SCR 6) to Factor H Binding Protein fromNeisseria meningitidisand the Binding of Factor H SCR 18 to 20 toNeisseria gonorrhoeaePorin

Abstract: Both Neisseria meningitidis and Neisseria gonorrhoeae recruit the alternative pathway complement inhibitory protein factor H (fH) to their surfaces to evade complement-dependent killing. Meningococci bind fH via fH binding protein (fHbp), a surface-exposed lipoprotein that is subdivided into three variant families based on one classification scheme. Chimeric proteins that comprise contiguous domains of fH fused to murine Fc were used to localize the binding site for all three fHbp variants on fH to short conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 55 publications
1
45
0
Order By: Relevance
“…Microbial proteins that bind Factor H and FHL-1 via these domains include Rck from Salmonella enterica and Gpm1 and Pra1 from C. albicans (23,35,44,45). A second group of microbial surface proteins binds the two human regulators either via SCRs 6-7 (e.g., M proteins and Fba from Streptococcus pyogenes, NspA from Neisseria meningitidis, CRASP-1 from B. burgdorferi) or via SCRs 18-20 (e.g., Scl1 from S. pyogenes and Por1B from Neisseria gonorrheae) of Factor H (30,(46)(47)(48). In addition, pathogenic microbes also bind the human terminal complement pathway regulator CFHR1.…”
Section: Discussionmentioning
confidence: 99%
“…Microbial proteins that bind Factor H and FHL-1 via these domains include Rck from Salmonella enterica and Gpm1 and Pra1 from C. albicans (23,35,44,45). A second group of microbial surface proteins binds the two human regulators either via SCRs 6-7 (e.g., M proteins and Fba from Streptococcus pyogenes, NspA from Neisseria meningitidis, CRASP-1 from B. burgdorferi) or via SCRs 18-20 (e.g., Scl1 from S. pyogenes and Por1B from Neisseria gonorrheae) of Factor H (30,(46)(47)(48). In addition, pathogenic microbes also bind the human terminal complement pathway regulator CFHR1.…”
Section: Discussionmentioning
confidence: 99%
“…These results are supported by the findings on a different panel of subvariants that were published by Dunphy et al (7) while our manuscript was under review. It has been elucidated that fHbp binds to short consensus repeat 6 (SCR6) of fH (50). Moreover, the nuclear magnetic resonance structure of the C-terminal portion of fHbp 1.1 (5) and the crystal structure of fHbp 1.1 in complex with fH SCR67 (48) have led to identification of residues important for binding of anti-fHbp antibodies and fH, respectively.…”
Section: Vol 79 2011 Analysis Of Fhbp Subvariants 977mentioning
confidence: 99%
“…fHBP binds preferentially to human fH, while chimpanzee, baboon, or rhesus macaque fHs show less binding or barely bind at all (84). The cocrystal structure of fHBP with human fH SCR6-7 peptide shows the host specificity between the divergent human and nonhuman primate fH SCR6 sequences that would interact with fHBP (61,84). The specificity of fHBP for human fH also helps to explain the observation that bactericidal titers measured with rabbit complement are typically higher than those measured in the presence of human complement (85,86).…”
Section: Evidence That Human Factor H Is the Ligand For Fhbpmentioning
confidence: 99%
“…Flow cytometric analysis has demonstrated that SCR domain 6 (SCR6) of fH is the main domain that interacts with fHBP on the surface of N. meningitidis (61). A cocrystal structure shows specific interactions involving both structural domains of fHBP (B24, variant 1.1) with the fH peptide that contains SCR domains 6 and 7 (fH 67 , one of the three SCR regions on fH involved in binding polyanions such as heparin), as shown in Fig.…”
Section: Evidence That Human Factor H Is the Ligand For Fhbpmentioning
confidence: 99%
See 1 more Smart Citation